Application of The Blinder-Oaxaca Decomposition Method to Analyze The Unemployment Gap Between Gender in Riau Province in 2022 - Widayati, Puji Wahyu; Harlen, Harlen; Maulida, Yusni (Westscience Press, 2024)
Gender equality is one of the goals of SDG, so every country needs to make efforts so that gender equality can be realized. Gender inequality is calculated using the Gender Inequality Index (GII). One of the components in preparing the Gender Inequality Index is labor force participation rate. Within the population included in the labor force, some people are employed and unemployed. In this study, gender inequality in terms of unemployment will be calculated using Blinder-Oaxaca decomposition with three calculation stages. The first is probit regression analysis, the second is marginal effects and the third is Oaxaca blinder decomposition. The results of the probit regression analysis show that all observed independent variables significantly effect on unemployment for both men and women. Meanwhile, the marginal effect results show that this variable’s influence is quite small, only 0.1 - 2 percent. The results of Oaxaca blinder decomposition show that the inequality between male and female unemployment is 1.42%, of which 29.88% is influenced by, observed factors and unobserved factors influence the remaining. There are only three variables that influence the gender gap, namely marital status, number of household members and household income 70.12%.